Cutaneous Manifestations of Child Abuse and Their Differential Diagnosis Blunt Force Trauma - Bilo, Robert A.C. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The skin is the most accessible organ of the body and also the most frequently injured organ in physical abuse of children. The interpretation of skin lesions, however, is not always simple. In recent years, many reports have been published on pediatric dermatological disorders and accidental injuries that were unjustly regarded as physical signs of child abuse. Knowledge of the differential diagnosis of unexplained skin findings is essential for accurate diagnosis and of vital importance given that errors in either direction (false positive or false negative) can have disastrous consequences.